Plight of honesty: untold bureaucracy - Sundaram, G. (New Delhi, 2008)
The book highlights the policy issues of the government in detail and the various vested interests (internal or external) in framing these policies. A separate chapter has been devoted to 'Bofors' or 'Tehelka' or 'Corruption' and another is on 'Bureaucracy'.
Keywords: Bureaucracy